PERBANDINGAN METODE SIRKUMSISI MODERN (KLAMP DAN LEM) TERHADAP PROSES PENYEMBUHAN LUKA PASCA SIRKUMSISI PADA ANAK - Ari Damayanti Wahyuningrum (Jurnal Ilmiah Kesehatan Media Husada, 2020)
Circumcision is a minor surgical procedure permormed as a modification of part the body by making an incision in the prepurtium of a part of the body by making incision in the prepurtium. The prepurtium that has not been circumcised has bacterial colonies which are risk factor for urinary tract infections. The insidence rate of urinary tract infections in Indonesia in infants who have not been circumcised under 1 year is 35% and children over 1 year are 22% of 200 children. The tecnology that eveloved in circumcision from the conventional methode of suture has shifted to the modern method of seamless circumcision. This study aims to compare the clamp and glue methods to the wound healing process after circumcision in chlidren. The research method was cohort with comparative statistical analysis of Pvalue 0.000<0.05 so there is a significant difference between the result of the klamp method ang glue in the healing process. Where the wound healing process in the glue method is much faster than the klamp method because it is more optimal in the hemostasis and inflammation phase because there are no foreign object namely the klamp. Keywords: Modern circumcision, Klamp, Glue, Wound Healing.